Pengaruh Kontrasepsi Hormonal Planibu® Versus Depo Progestin® terhadap Fungsi Hepar dan Profil Lipid - Djaswadi Dasuki, Olga Sanger, Flourisa J Sudradjat 3, Enny S Pamuji (Fakultas Kedokteran Universitas Gadjah Mada, 2008)
Background: Injectable contraception was used by about 15% of contraceptive users in Indonesia. Safety of injectable contraceptive was necessary to study before Planibu® was marketed in Indonesia. Safety was measured through liver function and lipid profile parameters.Objectives: To compare safety of Planibu® versus Depo Progestin® that was measured with liver function and lipid profile parameters Design of Study: “Double Blind Randomized Controlled Trial (Double Blind RCT)” Planibu® versus Depo Progestin®” nested on longitudinal surveillance and community based study in Purworejo district (LPKGM centre) and Manado municipality (Manado centre)Methods: Study population was childbearing age women, married and wanted to delay or space pregnancy with injectable contraceptive in Purworejo district and Manado municipality. Clinical, gynecological and laboratory examination was done before injectable contraceptive was administered. Laboratory examination included liver function SGOT, SGPT and lipid profile HDL, LDL and total cholesterol. Eligible Subjects who met inclusion and exclusion criteria were 70 women. As many as 35 women received Planibu® injection and 35 women received Depo Progestin® injection every 3 months for 12 months in the same time. Before injection was administered, venous blood sampling was taken from each subject.Results: Before using contraception, there was no statistical difference of liver function and lipid profile parameters between group Planibu® and Depo Progestin® (p>0,05). There was a statistically significant difference in the level of cholesterol, HDL, and SGOT during the 12 month of use Depo Progestin® (p=0,000, p=0,009 and p=0,000), although clinically it wasn’t significantly different. There was a statistically significant difference in the level of cholesterol, SGOT and SGPT during the 12 month of use Planibu® (p =0,038, p=0,000 dan p=0,018), although clinically it wasn’t significantly different. There was a statistically significant difference in the level of cholesterol and LDL during the 12 month of use Planibu® versus Depo Progestin® (p<0,05)Conclusion: There was a statistically significant difference in the level of cholesterol, HDL, and SGOT during the 12 month of use Depo Progestin®, although clinically it wasn’t significantly different. There was a statistically significant difference in the level of cholesterol, SGOT and SGPT during the 12 month of use Planibu®, although clinically it wasn’t significantly different. There was a statistically significant difference in the level of cholesterol and LDL during the 12 month of use Planibu® versus Depo Progestin®, although clinically it wasn’t significantly different. There was no difference clinically in the safety level of Planibu® versus Depo Progestin® shown by measurement result of liver function and lipid profile parameters.Keywords: planibu, depo progestin, liver, lipid